Modulation of electronic structure via dual moiré patterns in twisted 1 T -TaSe 2 - Yonghao Liu; Yuan Zheng; Kun Yang; Wenhao Zhang; Zongxiu Wu; Jingjing Gao; Xuan Luo; Yuping Sun; Jin Zhang; Yi Yin (Proceedings of the National Academy of Sciences, 2026)
We investigate a twisted bilayer of 1 T -TaSe 2 (twist angle < 4 ° ) using scanning tunneling microscopy and spectroscopy, revealing that the coexisting twisted atomic lattice and charge density wave (CDW) superlattice generate a dual moiré structure with distinct electronic modulation effects: The topographic moiré pattern stems from atomic lattice twisting modulating CDW intensity, while the twisted CDW superlattice drives a continuous insulator-to-metal transition, as evidenced by electronic gap evolution from large to metallic states. Density functional theory calculations show this transition arises from twist-induced changes in star of David motif stacking. Using the moiré-period gap map as the interlayer potential V ( r ) , we construct a continuum model via its Fourier components V G , finding that V G mediates multiple interlayer scattering processes that produce numerous superposition states manifesting as split flat-band pairs with distinct energy gaps. This work elucidates a CDW-twist-based mechanism for electronic control in 1 T -TaSe 2 and provides insights into Mott physics and complex electronic phases in related materials.